High‐intensity interval training and essential amino acid supplementation: Effects on muscle characteristics and whole‐body protein turnover - Hirsch, Katie R. (Physiol Rep, 2020)
The purpose of this study was to compare the independent and combined effects of high‐intensity interval training (HIIT) and essential amino acids (EAA) on lean mass, muscle characteristics of the quadriceps, and 24‐hr whole‐body protein turnover (WBPT) in overweight and obese adults. An exploratory aim was to evaluate potential modulatory effects of sex. Sixty‐six adults (50% female; Age: 36.7 ± 6.0 yrs; %BF: 36.0 ± 7.8%) were assigned to 8 wks of: (a) HIIT, 2 days/wk; (b) EAA supplementation, 3.6 g twice daily; (c) HIIT + EAA; or (d) control. At baseline, 4 wks, and 8 wks, total body, thigh LM and muscle characteristics were measured via dual‐energy x‐ray absorptiometry and B‐mode ultrasound, respectively. In a subsample, changes in WBPT was measured using [N(15)]alanine. Differences between groups were assessed using linear mixed models adjusted for baseline values, followed by 95% confidence intervals on adjusted mean change scores (Δ). HIIT and HIIT + EAA improved thigh LM (Δ: +0.17 ± 0.05 kg [0.08, 0.27]; +0.22 ± 0.05 kg [0.12,0.31]) and vastus lateralis cross‐sectional area (Δ: +2.73 ± 0.52 cm(2) [1.69,3.77]; +2.64 ± 0.53 cm(2) [1.58,3.70]), volume (Δ: +54.50 ± 11.69 cm(3) [31.07, 77.92]; +62.39 ± 12.05 cm(3) [38.26, 86.52]), and quality (Δ: −5.46 ± 2.68a.u. [−10.84, −0.09]; −7.97 ± 2.76a.u.[−13.49, −2.45]). Protein synthesis, breakdown, and flux were greater with HIIT + EAA and EAA compared to HIIT (p < .05). Sex differences were minimal. Compared to women, men tended to respond more to HIIT, with or without EAA. For women, responses were greater with HIIT + EAA than HIIT. In overweight and obese adults, 8 weeks of HIIT, with or without EAA, improved thigh LM size and quality; EAA may enhance muscular adaptation via increases in protein turnover, supporting greater improvements in muscular size and quality.